Association between triglyceride glucose-body mass index and all-cause mortality in critically ill patients with acute myocardial infarction: retrospective analysis of the MIMIC-IV database - Luo, Chaodi; Li, Qian; Wang, Zhuoer; Duan, Sifan; Ma, Qiang (Frontiers in Nutrition, 2024)
Background: Insulin resistance (IR) is closely related to the development of cardiovascular diseases.Triglyceride-glucose-body mass index (TyG-BMI) has been proven to be a reliable surrogate of IR, but the relationship between TyG-BMI and acute myocardial infarction (AMI) is unknown. The present study aims to determine the effects of TyG-BMI on the clinical prognosis of critically ill patients with AMI.The data of AMI patients were extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. All patients were divided into four groups according to the TyG-BMI quartile. Outcomes were defined as 30-day, 90-day, 180-day and 365-day all-cause mortality.Kaplan-Meier (K-M) curve was used to compare survival rate between groups. Meanwhile, Cox regression analysis and restricted cubic splines (RCS) were used to explore the relationship between TyG-BMI index and outcome events.Results: A total of 1188 critically ill patients with AMI were included in this study. They were divided into 4 groups according to TyG-BMI quartiles, there were significant differences in 90-day, 180-day, and 365-day all-cause mortality while there was no difference in 30-day all-cause mortality.Interestingly, with the increase of TyG-BMI, the 90-day, 180-day, and 365-day survival rate increased first and then gradually decreased, but the survival rate after decreasing was still higher than that in the group with the lowest TyG-BMI. U-shaped relationships between TyG-BMI index and 90-day, 180-day, and 365-day all-cause mortality were identified using RCS curve and the inflection point was 311.1, 316.5 and 320.1, respectively, whereas the TyG-BMI index was not non-linearly associated with 30-day all-cause mortality. The results of Cox proportional hazard regression analysis are consistent with those of RCS analysis.U-shaped relationships are existed between the TyG-BMI index and 90-day, 180-day and 365-day all-cause mortality in critically ill patients with AMI, but not 30-day all-cause mortality. The TyG-BMI index can be used as an effective index for early prevention of critically ill patients with AMI.